1997
DOI: 10.1089/neu.1997.14.839
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Cerebral Edema after Traumatic Brain Injury in Rats: Effects of Riluzole and Mannitol

Abstract: Brain trauma is the main cause of morbidity and mortality in young adults. One delayed events that occurs after a head trauma and compromises the survival of patients is cerebral edema. The present study examined first the occurrence of cerebral edema after a traumatic brain injury (TBI) induced by moderate fluid percussion in rats. Brain water content was measured from 1 h to 7 days posttrauma, in the hippocampus and cortex, on both ipsi- and contralateral hemispheres. Second, the effects of mannitol, an osmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(47 citation statements)
references
References 62 publications
5
42
0
Order By: Relevance
“…10,21 We observed an evolution of the contusion-related histological features similar to those described in more detail previously. 7,28 In previous rat experiments, others have shown that intra-and extracellular edema formation peaks from 12 hours to 2 days following contusion, 3,15 which corresponds to a peak in the intracranial pressure. 9 Many different descriptors are used for designating the physical properties of materials, and lay usage does not always equal the scientific definitions.…”
Section: Discussionmentioning
confidence: 94%
“…10,21 We observed an evolution of the contusion-related histological features similar to those described in more detail previously. 7,28 In previous rat experiments, others have shown that intra-and extracellular edema formation peaks from 12 hours to 2 days following contusion, 3,15 which corresponds to a peak in the intracranial pressure. 9 Many different descriptors are used for designating the physical properties of materials, and lay usage does not always equal the scientific definitions.…”
Section: Discussionmentioning
confidence: 94%
“…In this experimental model of TBI, edema develops early after trauma, increases within the first 15 h, and persists up to 48 h after injury (Bareyre et al, 1997). Our data showed that monotherapies and combination therapy reduced the posttraumatic brain edema by 70% at 24 h. More importantly, the combination still reduced 50% of the brain edema at 48 h after injury, exhibiting a potent long-lasting antiedematous effect, whereas fenofibrate and simvastatin, when given alone, had no more effect at this time point.…”
Section: Downloaded Frommentioning
confidence: 98%
“…In brief, the filtered mononuclear cell fraction was isolated using Ficoll-Paque PLUS (GE Healthcare Bio-Sciences Corp., New Jersey, USA) density gradient separation. The mononuclear cells were washed with human serum albumin in normal saline and adjusted to the appropriate concentration of 6×10 6 BMMNC/kg at a volume of 1cc/kg of body weight. Prior to release, the cells were tested for viability and presence of endotoxin.…”
Section: Methodsmentioning
confidence: 99%
“…The second and often long term goal is directed towards treating the secondary effects of the initial impact, which involves a neuroinflammatory response exacerbated by the breakdown of the blood brain barrier, resulting in sub-acute, life threatening cerebral edema. This second stage classically peaks approximately 48-72 hours after the initial trauma [5][6][7] . Subsequent chronic inflammation and cellular dysfunction manifests as chronic motor and cognitive disabilities.…”
Section: Introductionmentioning
confidence: 99%